2022
DOI: 10.31234/osf.io/daktp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognates are advantaged over non-cognates in early bilingual expressive vocabulary development

Abstract: Bilingual infants grow up with the unique experience of needing to learn two words for most concepts. These words are called translation equivalents, and translation equivalents that also sound similar (e.g., banana—banane) are called cognates. Research has consistently shown that children and adults process and name cognates more easily than non-cognates. The present study explored if there is such an advantage for cognate production in bilinguals’ early vocabulary development. Using longitudinal expressive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Specifically, we used data from Words & Sentences forms, which measure children's productive vocabularies. We used bilingual datasets from two origins: three datasets contributed to Wordbank (Frank et al., 2017; associated with Hoff et al., 2012, 2018; Legacy et al., 2018; Marchman et al., 2004), and one dataset (associated with Mitchell et al., 2022) openly available on the Open Science Framework, with a total of 2092 administrations from 518 children. These data were collected using the monolingual American English form and either the monolingual Mexican Spanish or the monolingual Quebecois French CDI form.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we used data from Words & Sentences forms, which measure children's productive vocabularies. We used bilingual datasets from two origins: three datasets contributed to Wordbank (Frank et al., 2017; associated with Hoff et al., 2012, 2018; Legacy et al., 2018; Marchman et al., 2004), and one dataset (associated with Mitchell et al., 2022) openly available on the Open Science Framework, with a total of 2092 administrations from 518 children. These data were collected using the monolingual American English form and either the monolingual Mexican Spanish or the monolingual Quebecois French CDI form.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, TEs vary in the degree of phonological similarity between the two items in each language—for example, dog [eng] and perro [spa] have no phonological overlap, whereas animal [eng] and animal [spa] are very similar phonologically. Indeed, previous research has suggested that TEs with greater phonological overlap are more likely to be TE pairs (Grasso et al., 2018; Umbel et al., 1992), and bilingual children produce more TE pairs that have high phonological overlap than TE pairs that have low phonological overlap (Bosch & Ramon‐Casas, 2014; Mitchell et al., 2022; Umbel et al., 1992). TEs can also vary in the lexical categories of their items: They could label, inter alia, objects, actions, or attributes, which broadly correspond to nouns, verbs, and adjectives.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of studies report the production of TEs in the early lexicon of bilingual children involving various language pairs, Romanian-Italian and Nigerian English-Italian (Barachetti et al, 2022), French-English (Jardak & Byers-Heinlein, 2018;Legacy et al, 2017;Poulin-Dubois et al, 2018), German, Spanish-English (Floccia et al, 2020), Spanish-English (Gimenez-Arce, 2019Shiro et al, 2020), German-English (De Anda & Friend, 2020), Spanish-Catalan (Mitchell et al, 2022), German-Indonesian . However, most studies on early lexical development in bilingual children involve language pairs from the Indo-European language family.…”
Section: Introductionmentioning
confidence: 99%